PENGARUH KEMAMPUAN MANAJERIAL DAN KONEKSI POLITIK TERHADAP REAKSI INVESTOR DENGAN KECURANGAN LAPORAN KEUNGAN SEBAGAI VARIABEL MEDIASI - Leonardus Matangkin; Suwandi Ng; Ana Mardiana (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2018)
This study aims to investigate the effect of managerial ability and political connections on fraudulent financial reporting, to investigate the effect of fraudulent financial reporting, managerial ability, and political connections on investor reaction, and aslo to investigate the effect of managerial ability and political connections on investor reactionmediated by fraudulent financial reporting.This study uses the whole company public listed in Indonesia Stock Exchange period 2015-2017, selected by purposive sampling method, which selects 134 firms each year,and using secondary data, i.e. the annual report and financial statements. The analytical method used is path analysis and hypothesis mediation analysed by using Sobel test.The results shows that managerial ability has a negative and significant impact on fraudulent financial reporting. Political connections have a positive and significant impact on fraudulent financial reporting and fraudulent financial reporting has a negative and significant impact on investor reaction. Managerial ability has a positive and significant impact on investor reaction and political connections has a negative and significant on investor reaction.This study also shows that fraudulent financial reporting play a role in mediating managerial ability on investor reaction, while fraudulent financial reporting do not play a role in mediating political connections on investor reaction.